2015
DOI: 10.1186/s40580-014-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transition metal doping (X = Co, Fe) on structural, optical properties of Ferroelectric Bi3.25La0.75X1Ti2O12

Abstract: Studies of the photoelectric properties of complex oxides have recently focused on materials with a narrow band gap because the wide band gap of complex oxides is one of the major obstacles limiting their use in photovoltaic cells. To tune the band gap of complex oxides, this study examined the effects of cobalt and iron doping on lanthanum-modified Bi 4 Ti 3 O 12 -based oxides (BLT) synthesized using a solid reaction method. The structural, optical and electrical properties of the synthesized powers were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Based on our previous results, the doping concentrations of Co and Fe atoms in the doped BLT targets were chosen to maximize the bandgap reduction, and the doping ratios were Bi 3.25 La 0.75 Co 1 Ti 2 O 12 (BLCT) and Bi 3.25 La 0.75 Fe 0.25 Ti 2 O 12 (BLFCT)2223. The BLT, BLCT, and BLFCT powders were blended thoroughly at the stoichiometric ratio in a ball mill for 24 h, dried in an oven at a temperature of 100 °C, and calcined at 700 °C for 2.5 h in air.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our previous results, the doping concentrations of Co and Fe atoms in the doped BLT targets were chosen to maximize the bandgap reduction, and the doping ratios were Bi 3.25 La 0.75 Co 1 Ti 2 O 12 (BLCT) and Bi 3.25 La 0.75 Fe 0.25 Ti 2 O 12 (BLFCT)2223. The BLT, BLCT, and BLFCT powders were blended thoroughly at the stoichiometric ratio in a ball mill for 24 h, dried in an oven at a temperature of 100 °C, and calcined at 700 °C for 2.5 h in air.…”
Section: Methodsmentioning
confidence: 99%
“…On other hand, the bandgap reducing by 0.4 eV in Zr doped Ti site of BiT [25], ∼0.9 eV with Co and ∼0. 73 eV with Fe doped Ti site in Bi 3.25 La 0.75 Ti 3 O 12 powders (but presenting secondary phase) [26] were reported. Han [26] reported that the second phase does not affect the bandgap, but might affect the ferroelectric response, which is a very important property for PVs applications.…”
Section: Introductionmentioning
confidence: 94%
“…Lanthanum-modified bismuth titanate powders (BLT) calcined at 700 °C were previously reported to crystallize with an orthorhombic structure. 21,22) The results showed that the XRD patterns of the samples calcined under 700 °C showed the incomplete formation of an orthorhombic BLT structure in the mixture state. Also, Besland et al 23) suggested that the optimal annealing temperature to crystallize BLT films by RF magnetron sputtering was above 650 °C.…”
Section: Resultsmentioning
confidence: 99%